Factors associated with treatment and control of hypertension in a healthy elderly population free of cardiovascular disease: A Cross-sectional Study - Chowdhury, Enayet; Nelson, M.R.; Ernst, M.E.; Margolis, K.L.; Beilin, L.J.; Johnston, C.I.; Woods, R.L.; Murray, A.M.; Wolfe, R.; Storey, E.; Shah, R.C.; Lockery, J.E.; et al. (OXFORD UNIV PRESS, 2020)
BACKGROUND: Despite readily available treatments, control of blood pressure (BP) with population aging remains suboptimal. Further, there are gaps in the understanding of the management of high BP in the aged. We explored antihypertensive treatment and control among elderly hypertensive participants free from overt cardiovascular disease (CVD), and identified factors related to both “untreated” and “treated but uncontrolled” high BP.